HPLC made to measure [ a practical handbook for optimization - Kromidas, Stavros (Wiley-VCH ; John Wiley, distribution, 2006)
The only topical HPLC book to focus on optimization, this volume addresses the needs of HPLC users who wish to constantly improve their methods, in particular in terms of throughput, accuracy and cost-effectiveness. This handbook features contributions from such bestselling authors as John W. Dolan, Michael McBrien, Veronika R. Meyer, Uwe D. Neue, Lloyd R. Snyder, and Klaus K. Unger, as well as from scientists working for major companies, including Agilent, AstraZeneca, Merck, Schering, Tosoh Biosep, VWR, and Waters. It covers essential aspects of optimization in general, optimization in diffe